L'emofiltrazione Come Test Diagnostico Dell'iperparatiroidismo Secondario - V. Panichi; A.M. Bianchi; B. Andreini; M. Migliori; S. De Pietro; L. Casarosa; L. Giovannini; R. Palla (AboutScience Srl, 1997)
Abstract non disponibile